Peculiarities Of Investigating Negligent Severe Or Moderately Severe Bodily Harm At The Initial Stage - Penzieva, Kateryna (Національний науковий центр «Інститут судових експертиз ім. Засл. проф. М.С. Бокаріуса», 2023)
One of the important stages in the development of a separate subtype methodology for investigating negligent severe or moderately severe bodily harm is the determination of the specifics of the initiation of criminal proceedings based on this fact and circumstances to be established during investigation of the specified criminal offense. Conducting a study of this issue will serve to eliminate the gap in forensic science, since currently the indicated methodology has not yet been developed. The Article purpose is to provide scientifically-based criminological recommendations regarding the specifics of initiating a pre-trial investigation into the infliction of negligent severe or moderately severe bodily harm. This includes outlining a set of investigative (search) and other procedural actions based on various typical investigative situations, with a focus on determining circumstances to be established during investigation of this crime. An analysis of investigative and judicial practices was conducted to study the methods used in investigating specific types of criminal offenses, peculiarities of initiating pre-trial investigations for the specified criminal offense. As a result, information sources about the committed crime have been determined.
Keywords: Investigation of negligent severe or moderately severe bodily harm, initial stage of investigation, typical investigative situation, circumstances to be established